THE THE EFFECT OF BANK INDONESIA CERTIFICATES, INFLATION, EXCHANGE RATE, GOVERNMENT REVENUE AND GOVERNMENT EXPENDITURE TO YIELD RETAIL SUKUK - Eri Hariyanto (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2022)
This study discusses the effect of Bank Indonesia Certificates, Inflation, Exchange Rate, Government Revenue, and Government Expenditure to Yield Retail Sukuk SR008 using the Vector Auto Regression (VAR) – Vector Error Correction Model (VECM) method. The result of this study based on the VECM test results, it can be concluded that a significant variable that positively influences yield in the short term are Inflation and Government Revenue variable. In the short term, inflation and government revenue affect the yield requested by investors. The government will respond to inflation fluctuations by changing Bank Indonesia Certificates, and ultimately this will affect yield. Declining government revenue will cause an increase in the issuance of SBN, and this in the law of demand and supply will affect yield. While in the long term, the variables that significantly affect positively are the Bank Indonesia Certificates, Inflation, Government Revenue. As in the short term, inflation and government revenue affect yield in long term. Then the variable that affects negatively is the Government Expenditure. As in the short term, government spending in the long term also does not affect the SR008 yield. As in the short term, inflation and state income affect yield.